Root and tuber crops: Untapped potential for food and nutrition security and rural livelihood development in Myanmar. Results of a scoping study. - Aung, M.; Prain, Gordon; Wheatley, Christopher C. (International Potato Center, 2018)
RTCs are not a priority crop in Myanmar, but there is still significant growth in production and demand, particularly potato and cassava. Information from farmers and other stakeholders in the RTC sector revealed various concerns and issues affecting RTC development in the study sites in terms of input supply, production, processing, and marketing. Initiatives for RTC development should focus on the accesibility of quality planting material, improved cultivation practice, small-scale mechanization, postharvest and processing facilities, and value chain development.